Experiential anatomy in dance technique eight skeletal explorations - Salk, Jennifer; Huey, Kesa.; Livingston, Chalie; University of Washington; Human Kinetics (Organization). (Champaign, IL : Human Kinetics, 2011)
'Experiential anatomy in dance technique will help instructors develop class material that allows their students to improve their understanding of their bodies -- and their ability to make educated choices about their movements while becoming more dynamic and versatile dancers. This DVD explores eight body areas: shoulder joint; scapula; hip joint; knee joint; spine; rib cage; tibia and fibula; and ankle, tarsus, and toes. For each area, the DVD features an instructor who identifies skeletal and anatomical features using a model skeleton, leads students in locating the anatomical features on themselves or on a partner, demonstrates movement explorations focusing on that body area, and choreographs phrases that explore that particular body area.'--Container.
'This DVD is designed to teach dance educators how to integrate anatomy into their technique classes without disruption to the flow of the class'--Opening credits.
Special features: interactive DVD tutorial has a multi-angle capability. Some tracks also contain additional audio commentary. DVD-ROM access to suggested reading material (.PDF).
Originally produced in 2011; c2008-2011 by the University of Washington.
Editor and DVD designer, Jeff Curtis ; Experiential anatomy in dance technique is the creation of Jennifer Salk, University of Washington, Dance Program.
Dancers : Kesa Huey, Chalie Livingston.
DVD format.
Keywords: Kinesiology, Applied; Muscles -- physiology